The Politics of Recognition in US-Philippine-Vatican Relations, 1898–1899. - Calacday, Jethro A E A (Diplomatic History, 2025)
The article explores the politics of recognition in US-Philippine-Vatican relations from 1898-1899, focusing on the treatment of Spanish friars by the Aguinaldo government. The Filipino nationalist Padre Mariano Sevilla praised his compatriots' conduct towards the vanquished Spaniards, emphasizing the need for unity to gain respect from other nations. The Vatican's refusal to recognize the First Philippine Republic facilitated US conquest, highlighting the complex interplay of diplomacy, religion, and sovereignty. The article sheds light on the role of the Roman Catholic Church in shaping international relations during this period, challenging traditional narratives of US empire expansion.